Corneal collagen cross-linking in paediatric patients affected by keratoconus. Issue 2 (27th June 2017) - Knutsson, Karl Anders; Paganoni, Giorgio; Matuska, Stanislav; Ambrosio, Oriella; Ferrari, Giulio; Zennato, Arianna; Caccia, Michela; Rama, Paolo
Abstract : Background/aims: To evaluate the effectiveness of corneal collagen cross-linking (CXL) in paediatric patients. Methods: Fifty-two eyes of 43 paediatric patients with progressive keratoconus were enrolled in a prospective cohort study. Corneal CXL was performed using a conventional technique with instillation of 0.1% riboflavin solution containing dextran 20% for 30 min during the soaking phase and during the 30 min ultraviolet A irradiation (3 mW/cm 2 ). Visual outcomes, topographic keratometry, maximum keratometry (K-max), refractive astigmatism, demarcation line and endothelial cell density were measured postoperatively. Results: A significant decrease of K-max from 59.30±7.08 to 57.07±6.46 (p<0.001) was observed 2 years after treatment. Uncorrected visual acuity improved from 0.59±0.41 LogMAR (logarithm of the minimum angle resolution) to 0.46±0.33 LogMAR (p=0.06) 2 years after the procedure, while best spectacle corrected visual acuity improved from 0.17±0.11 LogMAR to 0.15±0.12 LogMAR (p=0.17). Twenty-five eyes had K-max values of 60 dioptres (D) or greater. In this subgroup, K-max significantly decreased from 64.94±4.99 D to 62.25±4.42 D at 2 years (p<0.001). The demarcation line of the CXL treatment had a mean value of 249±74 µm and did not show a significant correlation with K-max flattening (Spearman r=0.019, p=0.899). Endothelial cell density remained stable 2 years after the procedure, changing from 2800±363 to 2736±659 cells/mm 2 (p=0.90). Conclusion: CXL is an effective treatment for avoiding keratoconus progression in paediatric patients. The procedure is safe and successful in stabilising keratoconus in eyes with more advanced forms of the disease, characterised by topographic K-max values greater than 60 D.